PROCEDURAL DEMONSTRATION AS A PRACTICAL LEARNING CONTRIVANCE TO AMELIORATE STUDENTS’ WRITING SKILL - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti; I Nyoman Suwandi; Anak Agung Rai Laksmi (International Journal of Linguistics and Discourse Analytics, 2020)
Writing is considered a difficult language skill for students to master comprehensively. Therefore, it is necessary to improve students' writing skills in a meaningful way. This paper is therefore intended to discuss students’ improvement in writing skills through executing a demonstration technique. The data were collected through administrating pre-tests, post-tests, and questionnaires. The result of the study showed that students had various obstacles in learning writing and they were struggling to obtain a higher level of knowledge in writing procedure texts, however, through a careful and intensive implementation of demonstration technique, students’ writing achievement improved significantly from session to session in all classroom writing practices. Students were not only able to write better procedure texts but their works are much worthy as well. In a nutshell, students’ writing needs continually enhancing and demonstration technique is very much recommended to be implemented in classroom writing activities as an alternative teaching technique.